Adaptation of a marine diatom to ocean acidification increases its sensitivity to toxic metal exposure. (October 2022) - Dai, Xiaoying; Zhang, Jiale; Zeng, Xiaopeng; Huang, Jiali; Lin, Jiamin; Lu, Yucong; Liang, Shiman; Ye, Mengcheng; Xiao, Mengting; Zhao, Jingyuan; Overmans, Sebastian; Xia, Jianrong; et al.
Abstract: Most previous studies investigating the interplay of ocean acidification (OA) and heavy metal on marine phytoplankton were only conducted in short-term, which may provide conservative estimates of the adaptive capacity of them. Here, we examined the physiological responses of long-term (~900 generations) OA-adapted and non-adapted populations of the diatom Phaeodactylum tricornutum to different concentrations of the two heavy metals Cd and Cu. Our results showed that long-term OA selected populations exhibited significantly lower growth and reduced photosynthetic activity than ambient CO2 selected populations at relatively high heavy metal levels. Those findings suggest that the adaptations to high CO2 results in an increased sensitivity of the marine diatom to toxic metal exposure. This study provides evidence for the costs and the cascading consequences associated with the adaptation of phytoplankton to elevated CO2 conditions, and improves our understanding of the complex interactions of future OA and heavy metal pollution in marine waters. Highlights: Adaptation to OA increased marine diatom's sensitivity to heavy metals (HM). OA-adapted cells decreased their growth and photosynthesis at high HM levels. The increase in sensitivity is associated with reduced metabolic activity.